The Sapa Seger Program as a Habit-Forming Strategy for Fostering Religious Character Among Students at SMP Muhammadiyah Plus Salatiga - Aas Lutfiana; Novita Dwi Setyowati; Purnomo Purnomo (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to examine the implementation of the Sapa Seger Program (Sabtu Pagi Semangat Gembira: Saturday Morning Enthusiasm and Joy) as a habituation strategy in shaping students' religious character at SMP Muhammadiyah Plus Salatiga. This research employs a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation. The results indicate that the Sapa Seger program is implemented in a structured and consistent manner, enabling the development of values such as faith, discipline, responsibility, and social awareness among students. The impact of the program is reflected in the improvement of religious practices, discipline, polite behavior, and students’ social awareness. Therefore, the Sapa Seger program is effective as a habituation strategy in shaping students' religious character and has implications as a model for strengthening character education in schools.